Differential impact of selective serotonin reuptake inhibitors on platelet response to clopidogrel: a randomized, double-blind, crossover trial - Hirsh-Rokach, Bruria; Spectre, Galia; Shai, Ela; Lotan, Amit; Ritter, Amit; Al-Aieshy, Fadiea; Malmström, Rickard E; Varon, David; Alcalai, Ronny (Pharmacotherapy, 2015)
To assess the effect of two selective serotonin reuptake inhibitors (SSRIs), fluvoxamine and citalopram, that markedly differ in their level of cytochrome P450 (CYP) 2C19 inhibition, on the laboratory response to clopidogrel, a prodrug requiring metabolism by the CYP system, and especially CYP2C19, to produce its active form. Randomized, double-blind, crossover trial. Clinical research unit of an academic medical center. Fifteen healthy male volunteers. All subjects received clopidogrel as a 300-mg loading dose on day 1, followed by 75 mg/day on days 2 and 3. Platelet function was tested at baseline and then after clopidogrel treatment on day 3. After a washout period of 2 weeks, subjects were randomly assigned in a double-blind manner to receive either citalopram 20 mg/day or fluvoxamine 100 mg/day for 7 days. On day 5, platelet function was tested while receiving the SSRI treatment alone; then, a 300-mg clopidogrel loading dose was administered, followed by clopidogrel 75 mg/day on days 6 and 7. Platelet function was then reassessed on day 7 while receiving the combination of the SSRI and clopidogrel. The treatment protocol was then repeated after a washout period of 2 weeks in all subjects with the other SSRI. The antiplatelet effects of fluvoxamine and citalopram and their interactions with clopidogrel were assessed. The response to these three drugs was assessed by light transmittance aggregometry and vasodilator-stimulated phosphoprotein phosphorylation, reporting P2Y12 receptor reactivity. Both fluvoxamine and citalopram tended to reduce adenosine diphosphate-induced aggregation: 80.8 ± 3.4% at baseline, 67.3 ± 6.3% while receiving citalopram, and 65.8 ± 6.4% while receiving fluvoxamine. All subjects had a good laboratory response to clopidogrel, with a mean aggregation of 23.5 ± 3.2% and a mean platelet reactivity index of 47.7 ± 3.9% (p<0.001 compared with baseline for both methods). Laboratory response to clopidogrel was significantly attenuated in the presence of fluvoxamine compared with the response in the presence of citalopram as tested both by aggregometry (32.3 ± 4.2% vs 23.4 ± 3%, p=0.04) and by vasodilator-stimulated phosphoprotein phosphorylation (52.7 ± 5.1% vs 35.9 ± 4.2%, p=0.02). Fluvoxamine attenuated the laboratory response to clopidogrel, possibly through inhibition of CYP2C19, whereas citalopram did not affect this response. These potential drug interactions should be taken into consideration in the selection of the appropriate antidepressant agent for patients who are treated with clopidogrel.